2021
DOI: 10.1007/s00595-020-02211-3
|View full text |Cite
|
Sign up to set email alerts
|

MRI pelvimetry-based evaluation of surgical difficulty in laparoscopic total mesorectal excision after neoadjuvant chemoradiation for male rectal cancer

Abstract: Purpose Laparoscopic total mesorectal excision (LaTME) is technically demanding in rectal cancer after neoadjuvant chemoradiotherapy (NCRT). This study aimed to predict the surgical difficulty of LaTME after NCRT based on pelvimetric parameters. Methods This study enrolled 147 patients who underwent LaTME after NCRT. The surgical difficulty was graded as high or low according to the operative time, estimated blood loss, conversion to open surgery, postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…The ischial spine spacing shows a trend toward an increased risk of TME specimen quality decline, and a shorter ischial spine spacing may be an independent risk factor for poor surgical quality [ 24 ]. Other research has also confirmed this [ 26 ]. Compared to open surgery, in the most distal anatomy of the mesorectum, lapTME is difficult to perform due to the curved angle of the sacrococcygeal bone, which can easily lead to low-quality TME specimens and increased rates of circumferential resection margin positivity [ 24 , 30 ].…”
Section: Influence Of a Difficult Pelvis On Rectal Cancer Surgerysupporting
confidence: 79%
See 2 more Smart Citations
“…The ischial spine spacing shows a trend toward an increased risk of TME specimen quality decline, and a shorter ischial spine spacing may be an independent risk factor for poor surgical quality [ 24 ]. Other research has also confirmed this [ 26 ]. Compared to open surgery, in the most distal anatomy of the mesorectum, lapTME is difficult to perform due to the curved angle of the sacrococcygeal bone, which can easily lead to low-quality TME specimens and increased rates of circumferential resection margin positivity [ 24 , 30 ].…”
Section: Influence Of a Difficult Pelvis On Rectal Cancer Surgerysupporting
confidence: 79%
“…1 ) [ 7 , 19 ] (k) Mesorectal fat area The area of mesangium and fat around the rectum at the level of the tip of the sciatic spine (Fig. 3 ) [ 13 , 23 , 25 , 26 ] (l) Angle T4 The angle between the upper and lower borders of the pubic symphysis with the lower border of the tumor as the vertex (Fig. 4 ) [ 31 ] (m) Angle A5 The angle between the line connecting the upper and lower borders of the pubic symphysis and the line connecting the midpoint of the upper border of the pubic symphysis to the sacral promontory (Fig.…”
Section: Imaging Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Defecation habits of patients are often changed in the middle phase of RC, such as slenderer or flatter stools. Some patients suffer from defecation frequency, tenesmus, anus discomfort, and hypogastrium pain [ 20 ]. At an advanced phase, bloody stool or mucus usually appears.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the median operative time and postoperative hospital stay were 310 min and 18 days, respectively, so those criteria were also adjusted accordingly. However, in the studies by Sun [ 18 ] and Chen [ 16 ], the average postoperative hospital stay was 8.0 days and 7.7 days, respectively. As a result, these authors adjusted the standard critical value of postoperative hospital stay to 7 days for analysis.…”
Section: Discussionmentioning
confidence: 99%